Electrospun microstructured biopolymer fibers containing the self-assembled Boc–Phe–Ile dipeptide : dielectric and energy harvesting properties - Handa, Adelino (2023)
Hybrid biomaterials were engineered using the electrospinning technique, incorporating the dipeptide Boc–L-phenylalanyl–L-isoleucine into microfibers composed of biocompatible polymers. The examination by scanning electron microscopy affirmed the morphology of the microfibers, exhibiting diameters ranging between 0.9 and 1.8 µm. The dipeptide self-assembles into spheres with a hydrodynamic size between 0.18 and 1.26 µm. The dielectric properties of these microfibers were characterized through impedance spectroscopy where variations in both temperature and frequency were systematically studied. The investigation revealed a noteworthy rise in the dielectric constant and AC electric conductivity with increasing temperature, attributable to augmented charge mobility within the material. The successful integration of the dipeptide was substantiated through the observation of Maxwell–Wagner interfacial polarization, affirming the uniform dispersion within the microfibers. In-depth insights into electric permittivity and activation energies were garnered using the Havriliak–Negami model and the AC conductivity behavior. Very importantly, these engineered fibers exhibited pronounced pyroelectric and piezoelectric responses, with Boc–Phe– Ile@PLLA microfibers standing out with the highest piezoelectric coefficient, calculated to be 56 pC/N. These discoveries help us understand how dipeptide nanostructures embedded into electrospun nano/microfibers can greatly affect their pyroelectric and piezoelectric properties. They also point out that polymer fibers could be used as highly efficient piezoelectric energy harvesters, with promising applications in portable and wearable devices.